Ornamenting 3D printed scaffolds with cell-laid extracellular matrix for bone tissue regeneration. (January 2015) - Pati, Falguni; Song, Tae-Ha; Rijal, Girdhari; Jang, Jinah; Kim, Sung Won; Cho, Dong-Woo
Abstract: 3D printing technique is the most sophisticated technique to produce scaffolds with tailorable physical properties. But, these scaffolds often suffer from limited biological functionality as they are typically made from synthetic materials. Cell-laid mineralized ECM was shown to be potential for improving the cellular responses and drive osteogenesis of stem cells. Here, we intend to improve the biological functionality of 3D-printed synthetic scaffolds by ornamenting them with cell-laid mineralized extracellular matrix (ECM) that mimics a bony microenvironment. We developed bone graft substitutes by using 3D printed scaffolds made from a composite of polycaprolactone (PCL), poly(lactic-co-glycolic acid) (PLGA), and β -tricalcium phosphate ( β -TCP) and mineralized ECM laid by human nasal inferior turbinate tissue-derived mesenchymal stromal cells (hTMSCs). A rotary flask bioreactor was used to culture hTMSCs on the scaffolds to foster formation of mineralized ECM. A freeze/thaw cycle in hypotonic buffer was used to efficiently decellularize (97% DNA reduction) the ECM-ornamented scaffolds while preserving its main organic and inorganic components. The ECM-ornamented 3D printed scaffolds supported osteoblastic differentiation of newly-seeded hTMSCs by upregulating four typical osteoblastic genes (4-fold higher RUNX2; 3-fold higher ALP; 4-fold higher osteocalcin; and 4-fold higher osteopontin) and increasing calcium deposition compared to bare 3D printed scaffolds. In vivo, in ectopic and orthotopic models in rats, ECM-ornamented scaffolds induced greater bone formation than that of bare scaffolds. These results suggest a valuable method to produce ECM-ornamented 3D printed scaffolds as off-the-shelf bone graft substitutes that combine tunable physical properties with physiological presentation of biological signals.